HYDRIDE FORMATION KINETICS ON GASEOUS HYDRIDING OF ZIRCALOY-4 USING AVRAMI EQUATION - Hadi Suwarno; Rohmad Sigit (Jurnal Sains Materi Indonesia, 2017)
HYDRIDE FORMATION KINETICS ON GASEOUS HYDRIDING OF ZIRCALOY-4 USING AVRAMI EQUATION. Zirconium alloys are mainly material for fuel cladding. Mechanical properties degradation of zircaloy-4 as nuclear fuel cladding is inevitable due to its interaction with hydrogen during normal reactor operation or transient condition. Kinetics analyses of Zircaloy-4 cladding materials at operating temperatures of 500, 550 and 600 oC under hydrogen atmosphere by using Avrami’s method to simulate brittle hydride phase formation and physical observation of the cladding after hydriding have been performed in order to observe the cladding to hydrogen interaction. Kinetic analyses showed that hydriding reaction rate follows the second order with activation energy of 35 kJ/mol. The formation of ε-ZrH phase, an indication of the physical degradation of the tubes, consumed time of 180 minutes at a temperature of 500 oC, 150 minutes at 550 oC, and 100 minutes at 600 oC, respectively. Degradation mechanical properties could be seen visually on the higher hydriding temperature. The cladding materials showed that the tube swelling occurs at a temperature of 550 oC and the tube degraded into pieces occurs at 600 oC. The value of mechanical degradation will be determined by mechanical testing in the next research.